1999
DOI: 10.1038/sj.bjc.6690681
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor A (VEGF-A) mRNA expression levels decrease after menopause in normal breast tissue but not in breast cancer lesions

Abstract: SummaryWe hypothesized that the regulation of microvascular functions and angiogenesis in breast tissue, a well known target of ovarian steroid action, is dependent on the hormonal exposure of the breast. Relative expression levels of VEGF-A (vascular endothelial growth factor A), a putative key regulator of angiogenesis in breast cancer, were analysed in the tumour and the adjacent non-neoplastic breast tissue of 19 breast cancer patients by quantitative reverse transcriptase polymerase chain reaction. In non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Indeed, it has been shown that VEGF-A is expressed by some breast cancer cell lines and is regulated by oestrogens and progestins (Hyder et al, 1998;Nakamura et al, 1996). VEGF-A expression in humans is significantly higher in pre-menopausal as compared to post-menopausal women indicating that steroid hormones also regulate VEGF expression in vivo (Greb et al, 1999). In addition to endothelial growth factors such as VEGF-A, the mammary gland also produces a number of vasodilatory compounds including parathyroid hormone-related protein (see Durban and Wysolmerski, pages 163-170, this issue), prostacyclin, nitric oxide, and endothelin.…”
Section: Control Of Mammary Angiogenesismentioning
confidence: 97%
“…Indeed, it has been shown that VEGF-A is expressed by some breast cancer cell lines and is regulated by oestrogens and progestins (Hyder et al, 1998;Nakamura et al, 1996). VEGF-A expression in humans is significantly higher in pre-menopausal as compared to post-menopausal women indicating that steroid hormones also regulate VEGF expression in vivo (Greb et al, 1999). In addition to endothelial growth factors such as VEGF-A, the mammary gland also produces a number of vasodilatory compounds including parathyroid hormone-related protein (see Durban and Wysolmerski, pages 163-170, this issue), prostacyclin, nitric oxide, and endothelin.…”
Section: Control Of Mammary Angiogenesismentioning
confidence: 97%
“…One of the main reasons for this limited efficacy is the propensity for malignant tumors to switch to production of other angiogenic molecules [44][45][46][47][48][49][50][51][52][53][54][55][56]. In the present study, we show that advanced stage breast tumors and mouse carcinomas expressed G-CSF and that inhibition of the cytokine in the 4T1 model prolonged the survival of the tumor-bearing mice.…”
Section: Cd34mentioning
confidence: 48%
“…Several studies show that VEGF-A, an angiogenic factor that is expressed in normal and transformed breast tissues [50,51], induces EPCs mobilization and differentiation into ECs [7,33]. The observation that VEGF inhibitors such as endostatin and bevacizumab suppress EPC recruitment and vascularization in mice [52] and patients with colorectal cancer [44,45] has strengthened the belief that VEGF plays a critical role in EPC generation and tumor vascularization.…”
Section: Cd34mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the decrease in VEGF has also been linked to the decline in oestrogen signalling in postmenopausal women [80] . Models of wound healing have shown that there is less induction of VEGF and basic FGF in response to injury in older animals [81,82] .…”
Section: The Infl Uence Of Age On Angiogenic Functionmentioning
confidence: 99%